Los nuevos vándalos y la Redacción Periodística - López de Zuazo Algar, Antonio (Estudios sobre el Mensaje Periodístico, 2002)
The terrorist Osama bin Laden, allied of the taliban in Afghanistan, said: “We will reconquer the Al Andalus”, Andalucía, the land of the vandals.